PENEGAKAN HUKUM TERHADAP PELAKU YANG MELAKUKAN TINDAK PIDANA PEMERASAN DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Lisda Desiana; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Extortion is an action that often occurs in people's daily life activities, extortioncan occur with various backgrounds and certain motives. Extortion in Dutch apersingand in English is called blackmail is a common crime. The word extortion in Indonesiancomes from the root word "squeezing" which can have the lexical meaning of "asking formoney and other types with threats".Type of research this can be classified into types of research sociological,because the study’s author lan gsung conduct research into the location or field poinythat in carefully in oerder to provide an overview as complete and clear about theprablem that ivestigated. Research is conducted in police of the Riau police while thepopulation and the sample is a whole party that is associated with a problem thatinvestigated in the study of this source of data that is used primary data secondary andthe data tertiary tecnique of collecting the data in the study is to interview and study ofliterature.From the results of the study, it can be concluded that law enforcement againstthe criminal case of extortion in Pekanbaru is still taking legal action in the form of aninvestigation or investigation to determine the suspect. The process of resolving the crimeof extortion, namely: the first with the investigation process, by collecting informationand a collection of documents or evidence, the second by carrying out a case title, thethird if in the implementation of the case title that the incident is a criminal act then aninvestigation is carried out by taking or collect evidence, examination, confiscation,search, arrest and detention. Meanwhile, the obstacles faced in law enforcement againstthe criminal act of extortion that occurred in the jurisdiction of the Pekanbaru city resortpolice were the lack of witnesses in handling cases of criminal acts of extortion so that ithindered the investigation process and Weakness in proving through words or threats bymouth making it difficult to prove. So the effort in overcoming the criminal case ofextortion is to complete the evidence based on Article 184 of the Criminal ProcedureCode in the form of: witness statements, expert statements, letters, instructions, andstatements from the defendant.Keywords: Law Enforcement – Domestic Violence – justice